2015
DOI: 10.1007/s10695-015-0059-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the physiological parameters, fatty acid metabolism, and SCD activity and expression in juvenile GIFT tilapia (Oreochromis niloticus) reared at three different temperatures

Abstract: We evaluated the effects of rearing temperature on the composition of fatty acids and stearoyl-CoA desaturase (SCD) activity and gene expression in GIFT (genetically improved farmed tilapia) tilapia. Three triplicate groups of fish were reared for 40 days at 22, 28, or 34 °C. At the end of the trial, the final body weight of juveniles reared at 28 °C was higher than that of fish reared at 22 or 34 °C. Feed intake, feed efficiency, and the protein efficiency ratio were also higher at 28 °C. The fatty acid compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 62 publications
(69 reference statements)
4
32
1
Order By: Relevance
“…For instance, a significant rise in serum enzyme activity (AST, ALT and ALP) may be an indication of liver damage including degeneration of the liver, necrosis and/or cellular damage (Akrami, Gharaei, Mansour, & Galeshi, ; Wang et al., ), which may result from the toxicity of certain dietary ingredients used in the formulation of experimental diets. On the other hand, elevated levels of TC, TG and LDL in the serum are considered an indicator of compromised health and immunity due to production and accumulation of excess amounts of reactive oxygen species (ROS; Ma, Qiang, He, Gabriel, & Xu, ). TP is used as an indicator of the nutritional and metabolic state of fish and is also considered an indicator of nonspecific immunity (Habte‐Tsion, ) while increased glucose as indicator of stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a significant rise in serum enzyme activity (AST, ALT and ALP) may be an indication of liver damage including degeneration of the liver, necrosis and/or cellular damage (Akrami, Gharaei, Mansour, & Galeshi, ; Wang et al., ), which may result from the toxicity of certain dietary ingredients used in the formulation of experimental diets. On the other hand, elevated levels of TC, TG and LDL in the serum are considered an indicator of compromised health and immunity due to production and accumulation of excess amounts of reactive oxygen species (ROS; Ma, Qiang, He, Gabriel, & Xu, ). TP is used as an indicator of the nutritional and metabolic state of fish and is also considered an indicator of nonspecific immunity (Habte‐Tsion, ) while increased glucose as indicator of stress.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al. () suggested that patterns of TC and HDL in the serum are likely to be correlated due to the fact that TC which exists in serum lipoprotein is transported from the artery walls to the liver for metabolism, therefore, with an increase in TC levels one can also expect an increase in HDL. This notion was certainly noted in this study as we found that both TC and HDL were significantly elevated at 0.5% BC supplementation, though TC was significantly improved at 2% BC supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the subcutaneous AT was found to have a greater MUFA proportion than the intramuscular fat (Sturdivant et al, ). Stearoyl‐CoA desaturase (SCD) is an enzyme abundant in animal tissues that converts 18:0 into 18:1 n‐9 (Ma et al, ; Sturdivant et al, ). It can be stimulated by low temperatures (Hsieh et al, ; Ma et al, ) and is closely related to changes in MUFA proportions (Hsieh et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Stearoyl‐CoA desaturase (SCD) is an enzyme abundant in animal tissues that converts 18:0 into 18:1 n‐9 (Ma et al, ; Sturdivant et al, ). It can be stimulated by low temperatures (Hsieh et al, ; Ma et al, ) and is closely related to changes in MUFA proportions (Hsieh et al, ). The SCD activity was shown to be especially great in subcutaneous AT of cattle (Chang et al, ; St. John et al, ), most likely to counterbalance the rumen biohydrogenation activity and increase MUFA proportions in subcutaneous AT.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in some fish, the HUFA levels measured as total lipids respond well to temperature changes, for example, in rainbow trout O. mykiss , salmon Salmo salar , and tilapia Oreochromis niloticus (Arts et al, ; Calabretti et al, ; Ma, Qiang, He, Gabriel, & Xu, ). In addition, temperature may also affect the ratio between phospholipids and neural lipids, although the total fat content in fish flesh remains constant (Calabretti et al, ).…”
Section: Discussionmentioning
confidence: 99%